Electoral competition with strategic disclosure - Jacopo Bizzotto; Benjamin Solow (Games, 2019)
Recent developments in information and communication technologies allow candidates for office to engage in sophisticated messaging strategies to influence voter choice. We consider how access to different technologies influence the choice of policy platforms by candidates. We find that when candidates can target messages to specific voter groups, platforms are more likely to be inefficient. In particular, when candidates can run targeted campaigns, they commit to projects that benefit small groups even when the social cost of these projects outweigh their benefits. Our results are robust to negative advertising.
Keywords: D72; D83; M37; 330; electoral competition; multidimensional policy space; microtargeting; office-motivated candidates; negative campaigning; strategic disclosure